2014
DOI: 10.1210/me.2014-1204
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Regulates Calcium Homeostasis in Lactation by Epigenetic Activation of Hedgehog Signaling

Abstract: Calcium homeostasis during lactation is critical for maternal and neonatal health. We previously showed that nonneuronal/peripheral serotonin [5-hydroxytryptamine (5-HT)] causes the lactating mammary gland to synthesize and secrete PTHrP in an acute fashion. Here, using a mouse model, we found that genetic inactivation of tryptophan hydroxylase 1 (Tph1), which catalyzes the rate-limiting step in peripheral 5-HT synthesis, reduced circulating and mammary PTHrP expression, osteoclast activity, and maternal circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 38 publications
3
43
0
1
Order By: Relevance
“…No literature has been found about the effect of 5-HT on the PTH receptors in the bone. Hernandez et al (2012) and Laporta et al (2014b) showed the stimulatory effect of increased 5-HT concentrations on the secretion of mammaryderived PTHrP in mice. As described in humans and mice, PTHrP acts on bone tissue to release calcium into the bloodstream (Wysolmerski, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…No literature has been found about the effect of 5-HT on the PTH receptors in the bone. Hernandez et al (2012) and Laporta et al (2014b) showed the stimulatory effect of increased 5-HT concentrations on the secretion of mammaryderived PTHrP in mice. As described in humans and mice, PTHrP acts on bone tissue to release calcium into the bloodstream (Wysolmerski, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Serotonin plays a role in bone remodeling as it is required for osteoclastogenesis (Chabbi-Achengli et al, 2012), and it regulates Ca transport into mammary epithelial cells during lactation (Laporta et al, 2014a). In response to lactation, serotonin produced by the mammary gland triggers production of PTH-related protein that stimulates osteoclast activity and increased bone mobilization (Laporta et al, 2014b). Because DCAD was shown to influence serotonin as cows approached calving, and treatment with 1,25-dihydroxyvitamin D 3 immediately after calving has been shown to increase serotonin in dairy cows (Vieira-Neto et al, 2017), it is clear that these dietary interventions can influence endocrine signals that affect nutrient flux to the mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…This secondarily upregulates TPH1/2, increasing 5HT synthesis while also decreasing 5HT degradation [ 28 ]. We have previously demonstrated an epigenetic-hedgehog link between 5HT and PTHrP involving DNA methylation [ 29 ]. However, 5HT has no donatable methyl groups, suggesting a secondary mechanism or indirect regulation of DNA methylation.…”
Section: Introductionmentioning
confidence: 99%